Effect of Low-temperature Aqueous Extraction on Flavor, Functional Ingredients and in Vitro Bioactivities of Penthorum chinense Pursh Leaf Extracts - Yijun LIU; Wei XU; Xue TIAN; Xinyu LIU; Yongqing TANG; Xuan LIU; Qian LAI; Li ZENG; Gang LI; Feixia DUAN (Shipin gongye ke-ji)
Penthorum chinense Pursh (PCP) leaf was a new food material for botanical beverage production, with bioactivities of antioxidant, hepatoprotective and anti-alcoholism but showing unpleasant flavors, especially for the high-temperature aqueous extracts. Accordingly, to reduce its unfavorable flavor with no effect on its health benefiting, the low-temperature aqueous extract (PLE50) was prepared by optimal low-temperature extraction. With the maximum aqueous solubility at 14.2 mg/mL, PLE50 showed the concentrations of phenols, flavonoids, gallic acid, quercetin, and pinocembrin at 1.90, 1.41 mg/mL, 49.98, 23.57 and 11.93 μg/mL, respectively, being significantly (P<0.05) higher than water brewed PCP soup. The results of HS-SPME-GC-MS revealed that safranal and 2,4-ditert-butylphenol were the primary sources of the unfavorable flavors in the boiling water extract of PCP leaves (PLE95), which contributed 54.43% and 5.89% to the overall flavor, respectively. Conversely, PLE50 showed little contents of safranal and 2,4-ditert-butylphenol with flavor contribution less than 0.1%. The major aroma components of PLE50 include decanal, β-cyclocitral, linalool, β-ionone, undecanal, 2-undecanone, 2-decanone, D-limonene, and dodecanal, contributing 76.97% to its flavor, which significantly (P<0.05) improved the sensory acceptability of PLE50. Besides, PLE50 showed the half scavenging concentrations for DPPH, ABTS+, and hydroxyl radicals at 0.034, 0.087, and 0.91 mg/mL, respectively, with 2.26 mmol/L ferric ion reducing power at the concentration of 1.6 mg/mL. PLE50 at 14.2 mg/mL exhibited the maximum activation rates at 183.33% for alcohol dehydrogenase and 951.88% for aldehyde dehydrogenase, being better than PLE95 at the same concentration. In summary, the optimal low-temperature aqueous extraction improved the flavor and sensory acceptability of PCP extracts, and maintained its in vitro antioxidant activity, as well as its activation capabilities for alcohol dehydrogenase and aldehyde dehydrogenase.